Nelumbo nucifera promotes non-rapid eye movement sleep by regulating GABAergic receptors in rat model. (1st March 2021) - Jo, Kyungae; Kim, Singeun; Hong, Ki-Bae; Suh, Hyung Joo
Abstract: Ethnopharmacological relevance: Nelumbo nucifera are used in folk medicine for anti-depressant, anti-convulsant, neuroprotective, and many other purposes. Aim of the study: The present work evaluated the sleep potentiating effects of water extract from lotus seed in rat, and the neuropharmacological mechanisms underlying these effects. Materials and methods: Pentobarbital-induced sleep test and electroencephalogram (EEG) analysis were applied to investigate sleep latency, duration, total sleeping time and sleep quality of Lotus extract. In addition, real-time PCR and HPLC analysis were applied to analyze the signaling pathway. Results: We found that the amounts of the possible active compounds GABA (2.33 mg/g) and L-tryptophan (2.00 mg/g) were higher than quinidine (0.55 mg/g) and neferine (0.16 mg/g) in lotus seed extract. High dose (160 mg/kg) administration of lotus extract led to a tendency towards decreased sleep latency time and an increase in sleep duration time compared to the control group in a pentobarbital-induced sleep model ( p  < 0.05). After high dose administration, total sleep and NREM were significantly increased compared to control, while wake time and REM were significantly decreased. Lotus extract-treated rats showed significantly reduced wake time and increased sleep time in a caffeine-induced model of arousal. The transcription level of GABAA receptor, GABAB receptor, and serotonin receptor tended to increase with dose, and lotus extract showed a strong dose-dependent binding capacity to the GABAA receptor. Conclusion: The above results strongly suggest that GABA contained in lotus seed extract acts as a sleep potentiating compound, and that sleep-potentiating activity involves GABAA receptor binding. Graphical abstract: Image 1 Highlights: Nelumbo nucifera seed extract led to decreased latency time of sleep in mice. Nelumbo nucifera seed extract increased NREM and total sleep time in rat. Nelumbo nucifera seed extract effectively relieves caffeine-induced sleep disturbance. Nelumbo nucifera seed extract played a GABAergic and serotonergic action. GABA contributed to sleep-promoting effect of the extract.